Hollow Co‐Based Layered Double Hydroxide Decorated with Ag Nanoparticles for the Oxygen Evolution Reaction. Issue 8 (22nd April 2022) - Gan, Xingyu; Guo, Xinjie; Li, Suozhu; Wang, Yun; Wang, Fengxiang; Lv, Xiaoxia
Abstract: Developing cost‐effective and efficient oxygen evolution reaction (OER) catalysts is very important for electrochemical water splitting devices. Herein, hollow Co‐based layered double hydroxide (LDH) decorated with Ag nanoparticles (Ag@H−Co‐−LDH) was constructed using ion etching of zeolitic imidazolate frameworks‐67 (ZIF‐67), followed by simple stirring with Ag salts. Hollow double layered structure could expose rich active centers and improve electron transfer and mass transport. Meanwhile, the introduction of Ag species greatly increases the electrical conductivity and enhances cobalt species to form highly catalytically active Co 4+ . Therefore, the as‐obtained Ag@H−Co−LDH exhibits a distinguished OER activity with a low overpotential of 298 mV to provide an oxygen evolution current density of 10 mA cm −2, which is superior to that of Co−LDH and even commercial RuO2 . Abstract : A hollow Co‐based layered double hydroxide (LDH) decorated with Ag nanoparticles (Ag@H−Co−LDH) is presented. This material exhibits an excellent electrocatalytic oxygen evolution reaction activity and a good stability due to the high valence of the cobalt from the in situ redox reaction between Ag and the LDH, and to the excellent charge and mass transport from the hollow structure and Ag dopants.